The world's oldest profession? Employment-age profiles from the transactional sex market - Nicholas Wilson (IZA Journal of Labor Policy, 2019)
Standard labor market models predict that the likelihood of employment increases, hours worked increase, and individuals transition from less-skilled and temporary jobs to more skilled and more stable employment as they age. I examine the association between age and transactional sex work using national household surveys from Zambia, one of the few settings with general population surveys asking women about transactional sex and a relatively high documented prevalence of employment in transactional sex. My results indicate that the likelihood of employment in transactional sex sharply falls with age. Increased employment opportunities outside of transactional sex do not appear to explain the transactional sex employment-age profile and marital status appears to explain only a portion of it. These findings are consistent with the hypothesis that clients prefer younger transactional sex workers and suggest that policymakers implement interventions designed to reduce client demand for younger females.
Keywords: J10; J40; O10; R23; 330; age; employment; labor supply; transactional sex; Zambia